2021
DOI: 10.1088/1361-6501/abf25c
|View full text |Cite
|
Sign up to set email alerts
|

Light-scattering of tracer particles for liquid flow measurements

Abstract: A variety of modern flow measurement techniques use tracer particles that should accurately follow fluid motions and should scatter sufficient light to be detectable by imagining systems. These two requirements are at odds if they are to be full-filled by varying the tracer size. For this reason, other particle properties such as material, structure, and coating are also considered. While the effect of these properties on the particle response time can be estimated, it is challenging to quantify their effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Glass beads with the thin silver coating (SG02S40 Potters Industries) were used as tracer particles for planar PIV. These monodisperse tracers have a mean diameter of d p = 2 μm and a density of (Das & Ghaemi 2021). Their response time, , and settling velocity, , are 9.8 × 10 −7 s and 7.2 × 10 −6 m s −1 , respectively.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Glass beads with the thin silver coating (SG02S40 Potters Industries) were used as tracer particles for planar PIV. These monodisperse tracers have a mean diameter of d p = 2 μm and a density of (Das & Ghaemi 2021). Their response time, , and settling velocity, , are 9.8 × 10 −7 s and 7.2 × 10 −6 m s −1 , respectively.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…µm in diameter were used to seed the flows (SG02S40 Potters Industries). Das & Ghaemi [42] demonstrated that these small silver coated particles have strong side scattering and relatively consistent sizing. Synchronization between the camera and the laser was achieved using a programmable timing unit (PTU 9, LaVision GmbH) and DaVis 7.3 software (LaVision GmbH).…”
Section: Steady Shear Viscositymentioning
confidence: 99%